2022
DOI: 10.3390/brainsci12080961
|View full text |Cite
|
Sign up to set email alerts
|

Inattention, Impulsivity, and Hyperactivity among Individuals with Self-Reported Impaired Wound Healing

Abstract: Background: Inattention and impulsivity are common causes of accidents and injury. The aim of the current study was to examine the level of attention deficit (AD), hyperactivity, and impulsivity (HI) in individuals with and without self-reported impaired wound healing (IWH). Methods: A survey was conducted among N = 773 Dutch young adults, 18–30 years old. N = 198 were allocated to the IWH group and N = 575 to the control group. All participants completed the Attention Deficit Hyperactivity Disorder (ADHD) Rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…This study in young adults in Germany confirmed that mood, quality of life, and immune fitness are poorer among individuals with self-reported impaired wound healing compared to healthy controls. It extended previous knowledge on the possible impact of attentional deficits [19] by showing that individuals with self-reported impaired wound healing have poorer attention focusing, whereas attention shifting did not differ from healthy controls. During the COVID-19 pandemic, significant negative effects were seen on mood, quality of life, and immune fitness, which were most pronounced and often statistically significant for the two lockdown periods.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This study in young adults in Germany confirmed that mood, quality of life, and immune fitness are poorer among individuals with self-reported impaired wound healing compared to healthy controls. It extended previous knowledge on the possible impact of attentional deficits [19] by showing that individuals with self-reported impaired wound healing have poorer attention focusing, whereas attention shifting did not differ from healthy controls. During the COVID-19 pandemic, significant negative effects were seen on mood, quality of life, and immune fitness, which were most pronounced and often statistically significant for the two lockdown periods.…”
Section: Discussionsupporting
confidence: 79%
“…The aim of the current study was to evaluate the impact of COVID-19 and associated lockdowns on the mood, quality of life, and immune fitness of German young adults with self-reported impaired wound healing. Research conducted before the pandemic among the same age group in The Netherlands revealed that, compared to healthy controls, young adults with self-reported impaired wound healing reported poorer mood [17], poorer sleep [18], lower quality of life [17], impaired attention and increased impulsivity [19], and a poorer immune fitness [20]. One study revealed that during the pandemic, significant lockdown effects were evident for both healthy controls and the group with self-reported impaired wound healing [11].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research revealed that self-reported impaired wound healing in young adults was associated with poorer mood, attention deficits, reduced quality of life, and poorer immune fitness. 12 , 13 The psychological distress of having chronic wounds was also shown to be associated with increased susceptibility to experiencing immune-related complaints 14 and health issues such gastrointestinal complaints 15 or poor sleep and increased levels of experiencing insomnia. 16 Given these frequent comorbidities and their potential negative impact on both disease course and treatment compliance, 6 it is important to further investigate these factors.…”
Section: Introductionmentioning
confidence: 99%